Problem of creativity in native psychology [Проблема креативности в отечественной психологии] (in Russian) - Ivanchenko, Andreyanna; Иванченко, Андреянна Алексеевна; Іванченко, Андреянна Олексіївна (Кам’янець-Подільський : Аксіома, 2012)
Статья посвящена теоретическому обобщению отечественных исследований креативности как научного понятия и психического явления. Проведен сравнительный анализ понятий «креативность» и «творчество», а также терминов, обозначающих данные понятия. Обосновано положение о креативности как динамической жизне-созидающей направленности личности. Утверждается, что раскрытие креативности сопровождается положительной эмоцио-подпиткой, позитивогенностью настроения, минимумом био-энергозатрат и одновременно выступает профилактикой дестабилизирующих психо-соматических проявлений. This paper is dedicated to the theoretical summarizing of native investigations relating to the creativity like a scientific concept and mental phenomenon. The comparative analysis of creativity and creative life-orientation notions as well as the terms they signify has been carried out. The thesis of creative life-orientation like a dinamic life-creating directing vector has been proved. It is testified that the creative life-orientation’s disclosing is accompanied by a positive emotional injection, a genetically determined positiveness of mood, a minimum of bio-energetic expense that concurrently serves like a precaution against the destabilizing psychosomatic manifestations.
Keywords: креативность; жизне-созидающая направленность; креатив-эталон; био-энергозатраты; позитивогенность; creative life-orientation; creative person-model; dynamic; bio-energetic expense; positiveness